Políticas linguísticas e nacionalização do português de Moçambique - Macaringue, Ilídio Enoque Alfredo (2014)
In this paper, our focus lies on the analysis of linguistics politics and the sociolinguistics situation in Mozambique, due to the confluence of several languages and cultures, to understand the processes of nativization and nationalization of Portuguese language in that country. Throughout the work, we have used, on a regular basis, the term nationalization in order to highlight the underlying processes to the ownership of Portuguese in Mozambique, viewing the ideological and political basis of being a n official language and a national unity, State and Mozambican language. The interest in studying the topic is related to the ambivalence in the epistemological foundations of the country s linguistics politics, which called for formalizing the Portuguese language without nationalizing it, and nationalized Bantu languages, also known as indigenous languages. The official discourse typifies them as national languages, despite being geographically fragmented, i.e. without national territorial extension, without officializing them. Moreover, for the fact that we work professionally with Portuguese language, and that day by day there is evidence that the Portuguese in Mozambique walks on the sidelines of the official goal, i.e., the alleged replication of the Eu ropean standard characteristics, adopted as standard and official language and as a national unity in 1975, the nation s independence day, reason for which it is being modified by customary law and thespeakers usage as a result of crossing different languages and cultures, taking into account some of the studies, which include Goncalves (1996a, 1996b, 1998, 2010), Firmino (2006) and Mendes (2010). The analyzed data, arising from literary excerpts, newspapers and magazines, allowed us to assert that the European Portuguese is being nationalized as a result of its culturallinguistics and ideological-symbolic appropriation by Mozambicans, hence the rising of a different Portuguese in that country, under the perspective of Caesar and Cavalcanti (2007), who refer to different dialects of Portuguese not as variation or dialects, but as other languages, legitimated by socio-cultural and contextual use of language. Therefore, Mozambique s Portuguese should be regulated similarly to different treatments that the also called Camoes s language is assumed around the world. Also, the results showed, for example, that language politics are disjointed with the current sociolinguistic context of that country. Therefore, there is an urgent need of revising it in order t o cover linguistic and cultural diversity and frame many people, who are on the margins of a homogenized society, in the State s political and administrative system, taking into account that the culture that unites is also the culture that segregates. In order to understand the sociolinguistic contours that are taking place in that country, we resorted to various methodological procedures, such as a qualitative research, aided by Bortoni-Ricardo s interpretivist (2008) and Ginzburg s (1989) evidentiary paradigms.